Relationship between Tax Avoidance, Leverage and Dividend Policy on Company Value - Prameswari, Ida Ayu Nirma; Sari, Desak Made Mya Yudia (Jurnal Inovasi Akuntansi (JIA), 2024)
This study aims to provide empirical evidence of the influence of tax avoidance and leverage on company value with dividend policy as a moderating variable. The population of this study is all consumer goods sector companies listed on the Indonesia Stock Exchange for the period 2017 - 2022. The sampling technique used is purposive sampling technique and obtained as many as 114 number of observations. This study uses the Statistical Product and Service Solution (SPSS) program with Moderated Regression Analysis (MRA) as a tool to analyze the moderating effect of dividend policy on the tested sample. The results of the analysis provide evidence that tax avoidance has no effect on firm value while leverage has a positive effect on firm value. Then, dividend policy strengthens the negative relationship between tax avoidance and firm value, but is unable to moderate the relationship between leverage and firm value.